2015
DOI: 10.1051/limn/2015031
|View full text |Cite
|
Sign up to set email alerts
|

The response of river nitrification to changes in wastewater treatment (The case of the lower Seine River downstream from Paris)

Abstract: -In the early 2000s, most of the effluents from the Paris agglomeration (12 million inhabitants) were still discharged after only a standard activated sludge treatment of carbon, thus releasing a high ammonium load. This triggered the growth of nitrifying bacteria in the river and caused a deficit of dissolved oxygen concentration 200 km downstream, at the entrance of the estuarine area. From 2007 on, improvements of the wastewater treatment plant (WWTP) helped to nitrify most of the ammonium, and to denitrify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 45 publications
4
30
0
Order By: Relevance
“…As an example, the low oxygen concentrations observed in July 2001 must be related to wastewater treatment plant failure and associated releases of high ammonium and/or organic matter concentrations from the 6.5 million equivalent inhabitants wastewater treatment plant. This type of event has already been highlighted by Aissa-Grouz et al (2015). As a consequence, low oxygen concentrations has been observed in the data in July 2001.…”
Section: Assessment Of the Hydro-biogeochemical Model Simulationssupporting
confidence: 53%
See 1 more Smart Citation
“…As an example, the low oxygen concentrations observed in July 2001 must be related to wastewater treatment plant failure and associated releases of high ammonium and/or organic matter concentrations from the 6.5 million equivalent inhabitants wastewater treatment plant. This type of event has already been highlighted by Aissa-Grouz et al (2015). As a consequence, low oxygen concentrations has been observed in the data in July 2001.…”
Section: Assessment Of the Hydro-biogeochemical Model Simulationssupporting
confidence: 53%
“…Simultaneously, nitrate and phosphate concentrations increases during low flow, particularly in the 7th stream order, are most likely related to the lower dilution of point sources in the urbanized river basin, as commonly observed downstream of large sewage treatment plant effluents. In addition, the increase in nitrate is also related to higher nitrification rates resulting from higher ammonium concentrations and higher water residence time, as already observed in the Seine River Aissa-Grouz et al, 2015;Raimonet et al, 2017a). The biogeochemical impacts of river flow decrease are thus expected to be greater downstream of conurbations with major sewage treatment plant effluents.…”
Section: Spatializing Hydro-biogeochemical Impacts Under Future Climamentioning
confidence: 70%
“…Many previous studies have identified high‐nitrification rates near low‐salinity estuarine turbidity maxima (Iriarte et al 1996; Brion et al ; Damashek et al ) and have associted these high rates with particle‐dominated microbial communities, and with NH 4 + sorption and desorption, as well as elevated heterotrophic activity. Low‐salinity regions of estuaries have also been locations where extremely high‐wastewater discharges of NH 4 + have supported high‐nitrification rates (Lipschultz et al ; Gazeau ; Soetaert et al ; Aissa‐Grouz et al ) and contributed to oxygen depletion. While the nitrification bursts that occur during vertical mixing in seasonally stratified and hypoxic systems may be short lived (Horrigan et al ), they potentially contribute substantially to annual cycles of inorganic nitriogen species and can support denitrification in underlying sediments during this period (Kemp et al ).…”
Section: Discussionmentioning
confidence: 99%
“…NI was included with a maximum specific growth rate coefficient of 1E−4 MNH4MnormalO2normals. Ranges of NI rate coefficients can be found in the literature (Admiraal & Botermans, ; Aissa‐Grouz et al, ; Raimonet et al, ; Sheibley et al, ; Strauss et al, ). Half‐saturation constants for O 2 were (3.125E−6 M), CH 2 O (1.0E−4 M), and NO 3 − (8.064E−6 M).…”
Section: Methodsmentioning
confidence: 99%